A SHORT-TERM PERFORMANCE MONITORING AND EVALUATION OF A PHOTOVOLTAIC SYSTEM AT YABA COLLEGE OF TECHNOLOGY USING A DATA LOGGER (FULafia Journal of Science and Technology, 2026)
The increasing global demand for sustainable energy has amplified the relevance of solar photovoltaic (PV) systems. This study investigates the performance of a 40 W monocrystalline PV module monitored over a four-month period using a UX 120-006M data logger. The system was deployed on a rooftop in the Physical Science Department of Yaba College of technology Lagos, Nigeria, capturing real-time voltage and ambient temperature data at 60-second intervals. Additionally, electrical characterization was conducted using I-V measurements to derive key performance parameters including open-circuit voltage (Voc), short-circuit current (Isc), maximum power point (MPP), fill factor (FF), and overall efficiency. Results reveal a diurnal voltage pattern peaking at midday with values exceeding 22 V and a consistent average between 12–14 V. Ambient temperatures ranged from 26–34 °C, reflecting tropical climatic influence. An inverse correlation between voltage and temperature was observed, attributed to the negative temperature coefficient of silicon-based modules. Electrical testing yielded a maximum power output of 22.46 W at 11.51 V and 1.95 A, with a calculated efficiency of 9.71 %, significantly below the 15–22 % benchmark for monocrystalline modules. The low fill factor (0.48) suggests internal inefficiencies or environmental constraints. This underperformance underscores the importance of real-time monitoring for early fault detection and maintenance planning. Despite suboptimal efficiency, the system remains viable for educational or low-power off-grid applications. The integration of data logger technology presents a robust framework for enhancing PV system reliability and operational insight.
Keywords: Photovoltaic systems; Data logger monitoring; Temperature effects; Module efficiency